A Model of the Spread of Chlamydia Trachomatis - Michael, Ajao Olutunde; Adebowale, Adejumo O. (Darul Yasin Al Sys, 2025)
Chlamydia as sexually transmitted disease that has major occurrence in sub-Saharan African where Nigeria is predominant this create a necessity to be concern about its spread within the nation.The SEScITR model with six compartments (Susceptible, Exposed, Screened, Infectious, Treated, Recovered) of human population was formulated. The parameters in the model were obtained from literatures and some were assumed. The ordinary differential equations were obtained using Runge Kutta Fehlberg Method and analysis of our system of equations was done using Maple 2017. Simulated data obtained through RStudio were used and our analysis were done using deSolve package on Rstudio. The formulated model was further analyse to get the reproduction number which is 0.67. The local and global stability ofSEScITR modelwas investigated using Jacobian matrix and Lyapunov function respectively and the results shows that Chlamydia disease free equilibrium is locally and globally asymptotically since R0<1 i.e.R0 =0.67. Also, the endemic state of Chlamydia equilibrium is locally and globally stable when R0>1.